Microscopic evidence for liquid-liquid separation in supersaturated CaCO3 solutions - Wallace, A.; Hedges, L.; Fernandez-Martinez, A.; Raiteri, Paolo; Gale, Julian; Waychunas, G.; Whitelam, S.; Banfield, J.; De Yoreo, J. (The American Association for the Advancement of Science, 2013)
Recent experimental observations of the onset of calcium carbonate (CaCO3) mineralization suggest the emergence of a population of clusters that are stable rather than unstable as predicted by classical nucleation theory. This study uses molecular dynamics simulations to probe the structure, dynamics, and energetics of hydrated CaCO3 clusters and lattice gas simulations to explore the behavior of cluster populations before nucleation. Our results predict formation of a dense liquid phase through liquid-liquid separation within the concentration range in which clusters are observed. Coalescence and solidification of nanoscale droplets results in formation of a solid phase, the structure of which is consistent with amorphous CaCO3. The presence of a liquid-liquid binodal enables a diverse set of experimental observations to be reconciled within the context of established phase-separation mechanisms.